As above, so below: textual variation in the Paippalāda sūryā-sūkta - de Joseph, Kristen (Lingua Posnaniensis, 2019)
This contribution will address the variants among parallel versions of this hymn, with special attention to the Paippalāda version (of which a critical edition is currently in preparation), and how these variants reflect the different chronology, socio-religious goals and textual history of the different recensions.